Papua Conflict Resolution In Contemporary Counter-Insurgency Perspective Using Mystic Diamond - Sanra Michico Moningkey; Eri R. Hidayat; Bambang Wahyudi; Pudjo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The conflict shows that the escalation tends to heat up marked by a series of attacks on civilians, religious leaders and health workers in July 2022. The problems show relevance and are correlational in government policies in economic development and the Papuan independence referendum. The perspective of the authoritarian approach is transformed into human security based on democracy, security and economic stability. Weak guarding and monitoring of government policies has led to problems and various rejections, including the Law on new autonomous regions. The purpose of writing this scientific paper is to analyze government policies in responding to the Papuan conflict in terms of the counterinsurgency strategy. The writing of this scientific paper uses a qualitative method that emphasizes observing the phenomenon and substance of the meaning of the Papuan conflict phenomenon.The COIN Papua strategy was developed with the concept of a mystic diamond with the addition of supervising and overseeing government policies through a dual control system between the government and the civilian. This is useful for growing Papuan people's trust in the Indonesian government and improving its image internationally. In addition, it requires seriousness in constructive communication, dialogue framing and international diplomacy through the International Parliament for West Papua (IPWP), International Lawyer for West Papua (ILWP), United Liberation Movement for West Papua (ULMWP) as part of conflict resolution from a historical justice perspective. and memoria passionis